2017
DOI: 10.31234/osf.io/ef45x
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Conscious access in the near absence of attention: Critical extensions on the dual-task paradigm

Abstract: Whether conscious perception requires attention remains a topic of intense debate. While certain complex stimuli such as faces and animals can be discriminated outside the focus of spatial attention, many simpler stimuli cannot. Because such evidence was obtained in dual-task paradigms involving no measure of subjective insight, it remains unclear whether accurate discrimination of unattended complex stimuli is the product of automatic, unconscious processing, as in blindsight, or is accessible to consciousnes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 56 publications
(127 reference statements)
0
9
0
Order By: Relevance
“…Prospective investigations are also required to examine more precisely how our findings generalise over different categories of stimuli or stimulus feature differentiation. It has been shown that these aspects can interact with attention and metacognition (Stein & Peelen, 2017;Matthews et al, 2018). In addition, the precise influence of evidence-reliability remains to be elucidated in more extensive work as it has also been shown to affect confidence judgments and metacognition (Boldt, De Gardelle & Yeung, 2017;Bang & Fleming, 2018;Denison & al., 2018).…”
Section: Limitations and Further Questionsmentioning
confidence: 99%
“…Prospective investigations are also required to examine more precisely how our findings generalise over different categories of stimuli or stimulus feature differentiation. It has been shown that these aspects can interact with attention and metacognition (Stein & Peelen, 2017;Matthews et al, 2018). In addition, the precise influence of evidence-reliability remains to be elucidated in more extensive work as it has also been shown to affect confidence judgments and metacognition (Boldt, De Gardelle & Yeung, 2017;Bang & Fleming, 2018;Denison & al., 2018).…”
Section: Limitations and Further Questionsmentioning
confidence: 99%
“…Alternatively, it may be that tACS had a cumulative negative effect on cognitive performance, however, this is unlikely given the positive time-on-task effect observed in the first CFS experiment. Instead, our participant instructions did not emphasise the equal distribution of confidence for a given block, meaning that what we measured may not actually have reflect trial-by-trial fluctuation of confidence, but instead meta awareness of fatigue, attentional drift or mindwandering over blocks (Matthews et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The advantage of this non-parametric method is its robustness against violations of Gaussian equal variance. The area under this curve now represents metacognitive sensitivity (Matthews et al, 2018;Matthews et al, 2019).…”
Section: Experiments 3 (Cfs Meta-cognition)mentioning
confidence: 99%
“…The advantage of this non-parametric method is its robustness against violations of Gaussian equal variance. The area under this curve now represents metacognitive sensitivity (Matthews et al, 2018;Matthews et al, 2019).…”
Section: Experiments 3 (Cfs Meta-cognition)mentioning
confidence: 99%